A separator for sodium-ion batteries and a method for manufacturing the same
By using sulfonated NASICON-type solid electrolyte and aminated β-Al2O3 as functional fillers in the sodium-ion battery separator, the problems of insufficient ion conductivity and interfacial impedance in traditional separators are solved, and a separator with high ion conductivity and thermal stability is achieved, thereby improving the overall performance of sodium-ion batteries.
Patent Information
- Application Number
- CN202510537068.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-27
- Publication Date
- 2025-12-05
- Estimated Expiration
- 2045-04-27
AI Technical Summary
Existing sodium-ion battery separators are inadequate in terms of ion conductivity, interfacial impedance, and mechanical properties, making it difficult to meet the requirements of high-performance sodium-ion batteries.
A functional coating using sulfonated NASICON-type solid electrolyte and aminated β-Al2O3 as functional fillers is bonded to a base film by an adhesive to form a separating membrane with high ionic conductivity.
It improves the ionic conductivity and thermal stability of sodium-ion batteries, and enhances their rate performance and cycle stability.
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of sodium-ion battery, in particular to a separator for sodium-ion battery and a preparation method thereof. BACKGROUND
[0002] Sodium-ion battery (SIB) has broad prospects in the fields of energy storage and large-scale applications due to its abundant resources, low cost and good cycle stability. However, the commercial development of sodium-ion battery still faces many challenges, among which the performance of the separator is crucial to the safety, cycle life and rate performance of the battery.
[0003] Traditional lithium-ion battery separators are mainly made of polyolefins (such as polyethylene PE and polypropylene PP), which have good mechanical strength and chemical stability. However, such separators have poor adaptability in sodium-ion batteries, mainly in the following aspects: the polarity of sodium-ion electrolyte is relatively high, while the surface of polyolefin separator is hydrophobic, resulting in poor electrolyte wettability, affecting ion transport and interface stability; in addition, sodium ions have larger radius than lithium ions, and their migration speed is relatively slow, which can easily form dendrites at the negative electrode interface, puncture the separator and cause short circuit, and the migration rate of sodium ions at the interface of the traditional separator is low, which can easily form large interface impedance, affecting the rate performance and cycle stability of the battery.
[0004] In order to solve the above problems, in recent years, researchers have developed inorganic-organic composite separators by coating inorganic fillers or functional polymer coatings on the surface of traditional polymer separators to improve the sodium-ion transport capacity and enhance the wettability and thermal stability of the separator. However, the existing composite separators still have problems of insufficient ionic conductivity, high interface impedance or poor mechanical properties, which are difficult to meet the needs of high-performance sodium-ion batteries.
[0005] Therefore, it is urgent to develop a separator for sodium-ion battery with high ionic conductivity to improve the overall performance of sodium-ion battery. SUMMARY
[0006] The present application provides a separator for sodium-ion battery and a preparation method thereof, which has high ionic conductivity and can be used to improve the overall performance of sodium-ion battery.
[0007] In a first aspect, the application provides a separator for a sodium ion battery, comprising: a base film; and a functional coating layer arranged on at least one side of the base film; wherein the functional coating layer comprises a functional filler and a binder; the functional filler comprises sulfonated NASICON-type solid electrolyte and aminated β-Al2O3; and the mass ratio of the sulfonated NASICON-type solid electrolyte to the aminated β-Al2O3 is 1:0.2-0.5.
[0008] According to the application, the separator comprises a base film and a functional coating layer, the functional filler in the functional coating layer adheres to the surface of the base film through the binder, and the functional filler comprises sulfonated NASICON-type solid electrolyte and aminated β-Al2O3, wherein the sulfonated NASICON-type solid electrolyte and the aminated β-Al2O3 can synergistically enable the separator to have a relatively high ionic conductivity, and the thermal stability of both is relatively good, so the separator also has good thermal stability.
[0009] Specifically, the inventors found that using NASICON-type solid electrolyte and β-Al2O3 as the filler of the coating layer of the separator, although both have NASICON-type sodium ion solid electrolyte and β-Al2O3 have relatively high Na + conductivity, but the surface polarity of both is relatively low, and the wettability with the electrolyte is relatively poor, which can cause the impedance of sodium ion conduction between the electrolyte and the NASICON-type sodium ion solid electrolyte and the β-Al2O3 to be relatively large, and in addition, physical separation can occur between the NASICON-type sodium ion solid electrolyte and the β-Al2O3, which can cause the local ion conduction path to be interrupted, affecting the sodium ion conduction performance. The related art focuses on using a silane coupling agent to combine the NASICON-type sodium ion solid electrolyte and the β-Al2O3, which to some extent overcomes the problem of local ion conduction interruption caused by physical separation of the two, but the silane coupling agent coated on the surface of the two has a negative impact on sodium ion conduction.
[0010] Based on this, the inventors discovered that using sulfonated NASICON-type solid electrolyte and aminated β-Al2O3 as functional fillers for the coating can effectively improve the above-mentioned problems. Sulfonation modification of the NASICON-type solid electrolyte can effectively improve its surface polarity, and the sulfonic acid groups on the surface can form reversible ionic bonds with sodium ions. At the same time, it can enhance the sodium ion solvation effect at the interface, making it easier for sodium ions to desolvate and migrate rapidly into the NASICON-type solid electrolyte. Thus, the sulfonated NASICON-type solid electrolyte can provide an efficient sodium ion conduction pathway. However, when using sulfonated NASICON-type solid electrolyte alone as a functional filler, the strong adsorption of sodium ions by the sulfonic acid groups may lead to uneven distribution of sodium ions at the interface, forming local high-concentration areas. This causes sodium ions to accumulate at the interface, resulting in interface polarization, affecting the continuity of sodium ion conduction and the sodium ion conduction rate. At the same time, due to the effect of electrostatic repulsion, the sulfonated NASICON-type solid electrolytes are not easy to contact each other and cannot form additional ion channels. The sodium ion conduction between particles is mainly carried out through the electrolyte, and the interfacial impedance also affects the sodium ion conduction rate.
[0011] Furthermore, by adding a certain amount of aminated β-Al2O3, the amino groups on the surface of aminated β-Al2O3 can form hydrogen bonds or ion pairs with sulfonic acid groups, enhancing the interfacial interaction between NASICON-type sodium ion solid electrolyte and β-Al2O3. This allows it to fill the spaces between sulfonated NASICON-type solid electrolytes (making the fillers no longer just bonded by binders, but forming pathways between the fillers). Since the layered structure of β-Al2O3 is conducive to the diffusion of sodium ions, it can form additional sodium ion conduction pathways, making the conduction pathways of sodium ions in the filler more continuous. At the same time, the amino groups on the surface of aminated β-Al2O3 can also reduce the accumulation of sodium ions at the interface of sulfonated NASICON-type sodium ion solid electrolytes, synergistically increasing the additional sodium ion conduction pathways with β-Al2O3, thereby effectively reducing interfacial polarization and improving the sodium ion conduction rate.
[0012] Therefore, by using a certain mass ratio of sulfonated NASICON-type solid electrolyte and aminated β-Al2O3 as functional fillers for the coating, a separator with high ionic conductivity can be obtained in this application, which can be used to improve the overall performance of sodium-ion batteries.
[0013] In some embodiments, the functional filler further includes aminated porous silica, and the mass ratio of the sulfonated NASICON-type solid electrolyte to the aminated porous silica is 1:0.1 to 0.2.
[0014] In some of the above embodiments, the inventors discovered that by further adding a certain amount of aminated porous silica to the functional filler, the ionic conductivity of the separator can be further improved. This may be because, although the sulfonated NASICON-type solid electrolyte and aminated β-Al₂O₃ have increased surface polarity through sulfonation and amination, their structures are relatively dense, resulting in fewer penetration paths for the electrolyte in the functional coating. Aminated porous silica can be dispersed in the coating, and its pore structure can adsorb the electrolyte through capillary action, effectively increasing the electrolyte's penetration path into the coating. This increases the electrolyte's wetting and liquid-retaining effects on the separator, promotes contact between the electrolyte and the filler, and improves the sodium ion transport path. Simultaneously, the amino groups on the surface of the aminated porous silica can combine with the sulfonated NASICON-type solid electrolyte through hydrogen bonds or ion pairs. The pores of the adsorbed electrolyte, combined with the amino groups on the surface, synergistically with aminated β-Al₂O₃, can further reduce the interfacial polarization of the sulfonated NASICON-type solid electrolyte, resulting in a separator with better ionic conductivity.
[0015] In some embodiments, the adhesive comprises a main adhesive and an adhesive aid, wherein the main adhesive comprises at least one of polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, and polytetrafluoroethylene; the adhesive aid comprises sulfonated polyether ether ketone, wherein the degree of sulfonation of the sulfonated polyether ether ketone is 40% to 60%; and the mass ratio of the main adhesive to the adhesive aid is 1:0.5 to 1.
[0016] In some of the above embodiments, the main binder has excellent mechanical strength and chemical resistance, which can effectively adhere the functional filler to the base film to form a stable functional coating and prevent the functional filler from detaching during the cycle use of the sodium-ion battery; the binder used includes sulfonated polyether ether ketone, which can significantly improve the wettability of the electrolyte to the coating. Combined with aminated porous silica, it can make the electrolyte more easily penetrate into the interior of the coating, thereby reducing the interfacial resistance of sodium ion conduction;
[0017] In addition, the sulfonic acid groups on the surface of sulfonated polyether ether ketone can provide additional sodium ion conduction channels through protonation. Under the action of electrostatic repulsion, the sulfonic acid groups of sulfonated NASICON solid electrolyte and sulfonated polyether ether ketone are more evenly distributed in the coating, which can also reduce the local high charge areas formed by excessive adsorption of sodium ions due to the aggregation of sulfonic acid groups and reduce polarization. Therefore, sulfonated polyether ether ketone can work synergistically with sulfonated NASICON solid electrolyte to further increase the transport path of sodium ions.
[0018] Meanwhile, the ether bonds in sulfonated polyether ether ketone can also reduce the activation energy of sodium ion migration, thereby reducing the excessive adsorption of sodium ions by sulfonate groups. Sulfonated polyether ether ketone with an appropriate degree of sulfonation can improve the migration ability of sodium ions in the coating. Therefore, when using the above-mentioned binder, the resulting separator membrane has better ionic conductivity.
[0019] It should be noted that although the sulfonic acid groups on sulfonated polyether ether ketone can increase the sodium ion conduction channels, if ordinary fillers are used, the strong adsorption capacity of the sulfonic acid groups, without the synergy of other functional fillers, may lead to excessive adsorption and affect the rapid conduction of sodium ions. Using it as a binder is designed for the functional coating of this application, which includes sulfonated NASICON-type solid electrolyte and aminated β-Al2O3. The synergy between them can make the separator membrane have better ionic conductivity.
[0020] In some embodiments, the polyvinylidene fluoride has a weight-average molecular weight of 400,000 to 1,000,000. As an example, in one embodiment of this application, polyvinylidene fluoride with a weight-average molecular weight of 600,000 is used.
[0021] In some embodiments, the sulfonated polyether ether ketone has a weight-average molecular weight of 60,000 to 120,000. As an example, in one embodiment of this application, a sulfonated polyether ether ketone with a weight-average molecular weight of 80,000 and a sulfonation degree of 50% was used, purchased from Dongguan Tianzhihong Plastic Co., Ltd.
[0022] In some embodiments, the adhesive further includes polyethylene oxide, wherein the mass ratio of the sulfonated polyether ether ketone to the polyethylene oxide is 1:0.3 to 1.
[0023] In some of the above embodiments, adding a certain mass of polyethylene oxide to the adhesive additive results in a separator with better ionic conductivity. This may be because polyethylene oxide has a strong affinity for sodium ions, which can solubilize sodium ions and further reduce the excessive aggregation caused by sulfonated polyether ether ketone and sulfonated NASICON-type solid electrolytes. This can further improve the sodium ion migration rate in the above coating system. At the same time, polyethylene oxide can make the coating more flexible and ductile, which is beneficial to improving the stability of the interface between the components of the coating during use, giving the coating a more stable sodium ion conduction pathway, thereby resulting in a separator with better ionic conductivity.
[0024] In some embodiments, the polyethylene oxide has a weight-average molecular weight of 100,000 to 200,000. As an example, in one embodiment of this application, polyethylene oxide with a weight-average molecular weight of 150,000 is used.
[0025] In some embodiments, the sulfonated NASICON-type solid electrolyte is obtained by treating a NASICON-type solid electrolyte with a sulfonating reagent, and the Dv50 of the NASICON-type solid electrolyte is 0.5 to 3 μm; the chemical general formula of the NASICON-type solid electrolyte is Na 3+x Zr 2-y M y Si 3-z P z O 12 , where 0 ≤ x ≤ 1, 0 ≤ y ≤ 2, 0 < z ≤ 2, and the M element is at least one of Mg, Zn, Ga, In, Y, Al, Ge, Sn, As, Fe, Sc, Sb, Cd, Ti, V, Co, Ni, Cr, Mn, Mo, Nb, Hf, La, Lu, Ta.
[0026] In some of the above embodiments, the sulfonated NASICON-type solid electrolyte is obtained by using a sulfonating reagent to treat the NASICON-type solid electrolyte with the above particle size and having the above chemical general formula. At this time, the obtained separator has better ionic conductivity.
[0027] In some embodiments, the sulfonated NASICON-type solid electrolyte is prepared by the following method: preheat and activate the NASICON-type solid electrolyte at 150 to 300 °C for 1 to 3 h, take 10 parts of the activated NASICON-type solid electrolyte and ultrasonically disperse it in 200 to 500 parts of dichloromethane, drop 10 to 15 parts of chlorosulfonic acid into the dispersion at 0 to 5 °C, heat to 45 to 60 °C and react for 6 to 12 h, filter and dry to obtain the product; then soak the above product in a 0.05 to 0.5 mol / L sodium hydroxide aqueous solution for 6 to 12 h, filter and dry to obtain the sulfonated NASICON-type solid electrolyte.
[0028] In some of the above embodiments, partial loss of sodium ions may occur during the sulfonation process. Therefore, after sulfonation, the product is soaked in a sodium hydroxide aqueous solution for sodium supplementation, so that the obtained sulfonated NASICON-type solid electrolyte, like the NASICON-type solid electrolyte, can supplement sodium ions in the coating and improve the ionic conductivity of the separator. <00oooo82>As an example, in an embodiment of the present application, a NASICON-type solid electrolyte with a Dv50 of 1 μm and a chemical general formula of Na3Zr2Si2PO 12 is used.
[0030] In some embodiments, the aminated β-Al₂O₃ is obtained by treating β-Al₂O₃ with an amination reagent, and the Dv50 of the β-Al₂O₃ is 0.5–3 μm. Based on the above embodiments, the aminated β-Al₂O₃ obtained by amination modification using β-Al₂O₃ with the above particle size results in a separator with better ionic conductivity.
[0031] In some embodiments, the aminated β-Al2O3 is prepared by dispersing 10 parts of β-Al2O3 and 15-40 parts of aminosilane coupling agent in 200-400 parts of ethanol aqueous solution and reacting at 75-90°C for 0.5-2 hours to obtain aminated β-Al2O3.
[0032] As an example, in one embodiment of this application, the Dv50 of β-Al2O3 is 1 μm.
[0033] In some embodiments, the amination-modified porous silica is obtained by treating porous silica with an amination reagent, wherein the porous silica has a Dv50 of 0.5–3 μm and a specific surface area of 50–300 m². 2 / g. Based on the above embodiments, the aminated porous silica obtained by amination modification using the above-mentioned porous silica with the above particle size and specific surface area results in a separator with better ionic conductivity.
[0034] In some embodiments, the aminated porous silica is prepared by dispersing 10 parts of porous silica and 20-40 parts of aminosilane coupling agent in 200-400 parts of ethanol aqueous solution, and reacting at 75-90°C for 0.5-2 hours to obtain aminated porous silica.
[0035] As an example, in one embodiment of this application, a Dv50 of 1.5 μm and a specific surface area of 168 m² are used. 2 / g porous silica.
[0036] In some embodiments, the mass ratio of the functional filler to the binder is 1:0.1 to 0.5. Based on the above embodiments, the binder binds the components together and stably adheres the coating to the base film, while the electrolyte has good wettability to the coating, and the separator has better ionic conductivity.
[0037] In some embodiments, the areal density of the functional coating is 5–20 g / m². 2 Based on the above embodiments, under the aforementioned conditions, the isolating membrane exhibits good ionic conductivity due to the areal density of the functional coating. As an example, in one embodiment of this application, the isal density of the functional coating is 10 g / m³. 2 .
[0038] In some embodiments, the base film is a polyolefin film with a thickness of 5–20 μm and an average pore size of 80–220 nm. As an example, in one embodiment of this application, a polypropylene film with a thickness of 9 μm and an average pore size of 130 nm is used.
[0039] In some embodiments, the functional coating is disposed on both sides of the base film.
[0040] It should be noted that, unless otherwise specified, the areal density of the functional coating refers to the areal density of the functional coating on one side.
[0041] Secondly, this application provides a method for preparing a separator for sodium-ion batteries, comprising: dispersing a functional filler and a binder in a solvent to obtain a functional coating slurry; wherein the functional filler comprises a sulfonated NASICON-type solid electrolyte and an aminated β-Al2O3; wherein the mass ratio of the sulfonated NASICON-type solid electrolyte and the aminated β-Al2O3 is 1:0.2 to 0.5; and coating the functional coating slurry onto at least one side of a base film to obtain a separator.
[0042] According to this application, the above method can prepare the separator membrane for sodium-ion batteries as described in the first aspect, thus having the beneficial effects of the first aspect and having good ionic conductivity.
[0043] It should be noted that the types and contents of functional fillers and binders in the functional coating can be selected according to the first aspect; the coating amount of functional coating slurry on the base film can be adjusted according to the areal density of the functional coating.
[0044] In some embodiments, the solvent includes at least one of diethylformamide, dimethylformamide, dimethylacetamide, and N-methylpyrrolidone. As an example, in one embodiment of this application, N-methylpyrrolidone and dimethylformamide are used as solvents in a volume ratio of 7:3.
[0045] In some embodiments, the solid content of the functional coating slurry is 10% to 50%.
[0046] Thirdly, this application provides a sodium-ion battery, including a separator membrane prepared according to any embodiment of the first aspect or a separator membrane prepared according to any embodiment of the second aspect.
[0047] According to this application, since the sodium-ion battery includes a separator membrane prepared according to any embodiment of the first aspect or the method described in any embodiment of the second aspect, the sodium-ion battery has better rate performance.
[0048] Compared with the prior art, the beneficial effects of this application are at least as follows:
[0049] By optimizing the components and their content in the functional coating set on at least one side of the base film, the sodium ion conduction path can be increased and the interfacial polarization can be reduced, resulting in a separator with high ionic conductivity. This separator can be used to prepare sodium-ion batteries and improve the overall performance of sodium-ion batteries, especially their rate performance. Detailed Implementation
[0050] The various embodiments or implementation schemes in this specification are described in a progressive manner, with each embodiment focusing on the differences from other embodiments.
[0051] In the description of this specification, the references to terms such as "one embodiment," "some embodiments," "illustrative embodiment," "example," "specific example," or "some examples," etc., indicate that a specific feature, structure, material, or characteristic described in connection with an embodiment or example is included in at least one embodiment or example of this application. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.
[0052] Furthermore, the terms "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of technical features indicated. Thus, a feature defined as "first" or "second" may explicitly or implicitly include at least one of that feature. In the description of this application, "multiple" means at least two, such as two, three, etc., unless otherwise explicitly specified.
[0053] In this specification, unless otherwise specified, "parts" refers to "parts by weight".
[0054] The following describes embodiments of this application. The embodiments described below are exemplary and are only used to explain this application, and should not be construed as limiting this application. Where specific techniques or conditions are not specified in the embodiments, they are performed according to the techniques or conditions described in the literature in this field or according to the product instructions. Reagents or instruments used, unless otherwise specified, are all conventional products that can be obtained commercially.
[0055] Preparation Example 1
[0056] Preparation of sulfonated NASICON-type solid electrolytes:
[0057] Na3Zr2Si2PO with a Dv50 of 1μm 12 After preheating and activation at 200℃ for 2 hours, take 10 portions of the activated Na3Zr2Si2PO4.12 The product was ultrasonically dispersed in 300 parts of dichloromethane to obtain a dispersion. 10 parts of chlorosulfonic acid were added dropwise to the dispersion at 0°C, and the mixture was heated to 50°C for 8 hours. The product was then filtered, washed, and dried to obtain the final product. This final product was then immersed in a 0.1 mol / L sodium hydroxide aqueous solution for 10 hours, filtered, washed with ethanol, and vacuum dried to obtain sulfonated Na3Zr2Si2PO4. 12 It is denoted as S-NASICON.
[0058] Preparation Example 2
[0059] Preparation of aminated β-Al2O3:
[0060] Ten parts of β-Al2O3 with a Dv50 of 1 μm were ultrasonically dispersed in 300 parts of ethanol aqueous solution (V / V = 50 / 50), and then 20 parts of 3-aminopropyltrimethoxysilane were added. The mixture was heated under reflux at 85 °C for 1 h, filtered and dried to obtain aminated β-Al2O3, denoted as N-β-Al2O3.
[0061] Preparation Example 3
[0062] Preparation of aminated porous silica:
[0063] Ten samples of Dv50 with a thickness of 1.5 μm and a specific surface area of 168 m² were tested. 2 / g of porous silica was ultrasonically dispersed in 300 parts of ethanol aqueous solution (V / V = 50 / 50), and then 30 parts of 3-aminopropyltrimethoxysilane were added. The mixture was heated and refluxed at 85°C for 1 hour. After filtration and drying, aminated porous silica was obtained, denoted as N-SiO2.
[0064] Example 1
[0065] Preparation of separator membranes for sodium-ion batteries:
[0066] Functional fillers and binders in a mass ratio of 1:0.2 were placed in a mixer, and solvent (N-methylpyrrolidone and dimethylformamide in a volume ratio of 7:3) was added. The mixture was dispersed at a stirring speed of 2000 r / min to obtain a functional coating slurry with a solid content of 20%. The functional fillers were S-NASICON, N-β-Al2O3 and N-SiO2 in a mass ratio of 1:0.4:0.1, and the binders were polyvinylidene fluoride and bonding aids in a mass ratio of 1:0.6. The bonding aids were sulfonated polyether ether ketone and polyethylene oxide in a mass ratio of 1:0.5.
[0067] The functional coating slurry was uniformly coated onto one side of a 9 μm thick polypropylene film with an average pore size of 130 nm using a doctor blade coating method. After drying in an oven, the slurry was coated onto the other side of the polypropylene film and dried in an oven to obtain a release film. The areal density of the functional coatings on both sides was 10 g / m². 2 .
[0068] Example 2
[0069] Preparation of separator membranes for sodium-ion batteries:
[0070] It is largely the same as Example 1, except that the functional filler is S-NASICON and N-β-Al2O3 in a mass ratio of 1:0.4.
[0071] Example 3
[0072] Preparation of separator membranes for sodium-ion batteries:
[0073] It is largely the same as Example 1, except that the adhesive is polyvinylidene fluoride and does not contain any adhesive additives.
[0074] Example 4
[0075] Preparation of separator membranes for sodium-ion batteries:
[0076] It is largely the same as Example 1, except that the adhesive is sulfonated polyether ether ketone and does not contain polyethylene oxide.
[0077] Example 5
[0078] Preparation of separator membranes for sodium-ion batteries:
[0079] It is largely the same as Example 1, except that the adhesive is polyethylene oxide and does not contain sulfonated polyether ether ketone.
[0080] Comparative Example 1
[0081] Preparation of separator membranes for sodium-ion batteries:
[0082] Similar to Example 1, except that the functional filler is Na3Zr2Si2PO4 with a Dv50 of 1 μm at a mass ratio of 1:0.4. 12 It contains β-Al2O3 with a Dv50 of 1 μm; the binder is polyvinylidene fluoride and does not contain any adhesive additives.
[0083] Comparative Example 2
[0084] Preparation of separator membranes for sodium-ion batteries:
[0085] Similar to Example 1, except that the functional filler is Na3Zr2Si2PO4 with a Dv50 of 1 μm at a mass ratio of 1:0.4. 12 β-Al2O3 with a Dv50 of 1 μm.
[0086] Comparative Example 3
[0087] Preparation of separator membranes for sodium-ion batteries:
[0088] Similar to Example 1, except that the functional filler is Na3Zr2Si2PO4 with a Dv50 of 1 μm at a mass ratio of 1:0.4. 12 and N-β-Al2O3.
[0089] Comparative Example 4
[0090] Preparation of separator membranes for sodium-ion batteries:
[0091] It is largely the same as Example 1, except that the functional filler is S-NASICON.
[0092] Comparative Example 5
[0093] Preparation of separator membranes for sodium-ion batteries:
[0094] The results are largely the same as in Example 1, except that the functional fillers are S-NASICON Dv50 and β-Al2O3 with a mass ratio of 1:0.4.
[0095] Comparative Example 6
[0096] Preparation of separator membranes for sodium-ion batteries:
[0097] It is largely the same as Example 1, except that the functional filler is S-NASICON and N-SiO2 in a mass ratio of 1:0.4.
[0098] Test section
[0099] Preparation of the 2032 coin cell for testing: In a vacuum glove box, a sodium sheet was placed in the negative electrode shell of the battery, and an electrolyte (a 1 mol / L NaClO4 solution of ethylene carbonate and propylene carbonate in a 1:1 mass ratio) was added. The separator to be tested was then placed in place, ensuring it adhered tightly to the sodium sheet. The same electrolyte was added again, and finally, the positive electrode (active material layer, by mass, sodium vanadium phosphate: conductive carbon black: polyvinylidene fluoride = 8:1:1, current collector being aluminum foil) was placed on top and sealed. The assembled coin cell was removed from the vacuum glove box and left to stand for 24 hours before testing.
[0100] Ionic conductivity test: at room temperature, on an electrochemical workstation, at 10 -1 ~106 The test was conducted within the Hz frequency range to obtain the isolation film resistance Rb, and the ionic conductivity σ (unit: mS / cm) was calculated using the following formula: σ=L / (Rb×S);
[0101] Where Rb is the equivalent resistance, and L and S are the thickness and area of the isolation membrane under test, respectively.
[0102] Table 1
[0103] Ionic conductivity (mS / cm) Example 1 2.36 Example 2 2.03 Example 3 1.83 Example 4 2.16 Example 5 2.02 Comparative Example 1 0.62 Comparative Example 2 0.86 Comparative Example 3 0.95 Comparative Example 4 0.97 Comparative Example 5 1.03 Comparative Example 6 1.19
[0104] As shown in Table 1, the ionic conductivity of the separators obtained in each embodiment is significantly higher than that of the comparative examples, indicating that the separators provided in this application have good conductivity for sodium ions, which is beneficial to improving the overall performance of sodium-ion batteries. This may be because Comparative Examples 1 and 2 use unmodified NASICON solid electrolyte and β-Al2O3 as functional fillers, which are only bonded together in the coating by an adhesive. The interfacial resistance of sodium ions migrating between particles is high, resulting in low ionic conductivity. In contrast, Comparative Example 2 uses sulfonated polyether ether ketone and polyethylene oxide as binding agents, which can appropriately reduce the interfacial resistance of sodium ion migration, thus its ionic conductivity is higher than that of Comparative Example 1.
[0105] In Comparative Example 3, unmodified NASICON solid electrolyte and aminated β-Al2O3 were used as functional fillers. Amination of β-Al2O3 alone could not effectively improve the physical separation between the two, resulting in high interfacial impedance between the fillers and low ionic conductivity.
[0106] Comparative Example 4 uses only sulfonated NASICON solid electrolyte as a functional filler. Although the sulfonate group can improve the migration rate of sodium ions, there may also be a problem of sodium ion aggregation. At the same time, due to electrostatic repulsion, the particles are mainly bonded by binders, so its ionic conductivity is relatively low.
[0107] In Comparative Example 5, sulfonated NASICON solid electrolyte and β-Al2O3 were used as functional fillers. Sulfonating only the NASICON solid electrolyte could not effectively improve the physical separation between the two. As a result, β-Al2O3 could not easily reduce the enrichment of sodium ions on the surface of the sulfonated NASICON solid electrolyte and could not significantly improve the ionic conductivity of the separator.
[0108] In Comparative Example 6, sulfonated NASICON solid electrolyte and aminated porous silica were used as functional fillers. Although aminated porous silica and sulfonated NASICON solid electrolyte are combined through hydrogen bonds or ion pairs, and the amino groups on the surface can reduce the aggregation of sodium ions to a certain extent, porous silica has a weak ability to promote the migration and diffusion of sodium ions and cannot significantly improve the ionic conductivity of the separator.
[0109] As can be seen from Examples 1 and 2, adding a certain amount of aminated silica can further improve the ionic conductivity of the separator.
[0110] As can be seen from Examples 1, 3 to 5, the use of adhesive additives and synergistic functional fillers can further improve the ionic conductivity of the separator. Furthermore, when using a certain mass ratio of sulfonated polyether ether ketone and polyethylene oxide, the ionic conductivity of the obtained separator is even higher.
[0111] In addition, the inventors placed the isolation film obtained in Example 1 in an oven at 130°C for 1 hour and tested its heat shrinkage rate. The longitudinal shrinkage rate and the transverse shrinkage rate were 1.2% and 0.8%, respectively, indicating that the isolation film provided in this application also has good thermal stability. This is also because the functional filler in this application has good stability and strength, so the isolation film also has good heat resistance.
[0112] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of this application, and are not intended to limit them. Although this application has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of this application.
Claims
1. A separator film for a sodium-ion battery, characterized by, The separator film comprises: a base film; and a functional coating layer arranged on at least one side of the base film; wherein the functional coating layer comprises a functional filler and a binder; the functional filler comprises sulfonated NASICON-type solid electrolyte, aminated β-Al2O3, and aminated porous silica; a mass ratio of the sulfonated NASICON-type solid electrolyte, the aminated β-Al2O3, and the aminated porous silica is 1:0.2-0.5:0.1-0.
2.
2. The separator film according to claim 1, characterized by the binder comprises a main binder and a binding aid, the main binder comprises at least one of polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, and polytetrafluoroethylene; the binding aid comprises sulfonated polyether ether ketone, and a sulfonation degree of the sulfonated polyether ether ketone is 40%-60%; a mass ratio of the main binder and the binding aid is 1:0.5-1.
3. The separator membrane according to claim 2, characterized in that, the binding aid further comprises polyethylene oxide, and a mass ratio of the sulfonated polyether ether ketone and the polyethylene oxide is 1:0.3-1.
4. The separator film according to claim 1, characterized by the sulfonated NASICON-type solid electrolyte is obtained by treating NASICON-type solid electrolyte with a sulfonation reagent, and a Dv50 of the NASICON-type solid electrolyte is 0.5-3 μm; The chemical general formula of the NASICON type solid electrolyte is Na 3+x Zr 2-y M y Si 3-z P z O 12 , wherein, 0<=x<=1, 0<=y<=2, 0 M is at least one of Mg, Zn, Ga, In, Y, Al, Ge, Sn, As, Fe, Sc, Sb, Cd, Ti, V, Co, Ni, Cr, Mn, Mo, Nb, Hf, La, Lu, Ta.
5. The separator membrane of claim 1, wherein the aminated β-Al2O3 is obtained by treating β-Al2O3 with an amination reagent, and a Dv50 of the β-Al2O3 is 0.5-3 μm.
6. The separator membrane of claim 1, wherein The aminated porous silica is obtained by treating a porous silica having a Dv50 of 0.5 to 3 pm and a specific surface area of 50 to 300 m 2 / g with an amination reagent.
7. The separator membrane of claim 1, wherein The separator film satisfies at least one of the following conditions: 1) a mass ratio of the functional filler and the binder is 1:0.1-0.5; 2) the functional coating has an areal density of 5 to 20 g / m 2 ; 3) the base film is a polyolefin film, a thickness of the base film is 5-20 μm, and an average pore size of the base film is 80-220 nm.
8. A method of preparing a separator membrane for a sodium-ion battery, characterized by, The method comprises: dispersing the functional filler and the binder in a solvent to obtain a functional coating layer slurry; the functional filler comprises sulfonated NASICON-type solid electrolyte, aminated β-Al2O3, and aminated porous silica; and a mass ratio of the sulfonated NASICON-type solid electrolyte, the aminated β-Al2O3, and the aminated porous silica is 1:0.2-0.5:0.1-0.2; coating the functional coating layer slurry on at least one side of the base film to obtain the separator film.
9. A sodium-ion battery, characterized in that, The separator film comprises: a base film; and a functional coating layer arranged on at least one side of the base film; wherein the functional coating layer comprises a functional filler and a binder; the functional filler comprises sulfonated NASICON-type solid electrolyte, aminated β-Al2O3, and aminated porous silica; a mass ratio of the sulfonated NASICON-type solid electrolyte, the aminated β-Al2O3, and the aminated porous silica is 1:0.2-0.5:0.1-0.
2. the binder comprises a main binder and a binding aid, the main binder comprises at least one of polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, and polytetrafluoroethylene; the binding aid comprises sulfonated polyether ether ketone, and a sulfonation degree of the sulfonated polyether ether ketone is 40%-60%; a mass ratio of the main binder and the binding aid is 1:0.5-1. the binding aid further comprises polyethylene oxide, and a mass ratio of the sulfonated polyether ether ketone and the polyethylene oxide is 1:0.3-1. the sulfonated NASICON-type solid electrolyte is obtained by treating NASICON-type solid electrolyte with a sulfonation reagent, and a Dv50 of the NASICON-type solid electrolyte is 0.5-3 μm; the aminated β-Al2O3 is obtained by treating β-Al2O3 with an amination reagent, and a Dv50 of the β-Al2O3 is 0.5-3 μm. The separator film satisfies at least one of the following conditions: 1) a mass ratio of the functional filler and the binder is 1:0.1-0.5; 3) the base film is a polyolefin film, a thickness of the base film is 5-20 μm, and an average pore size of the base film is 80-220 nm. The method comprises: dispersing the functional filler and the binder in a solvent to obtain a functional coating layer slurry; the functional filler comprises sulfonated NASICON-type solid electrolyte, aminated β-Al2O3, and aminated porous silica; and a mass ratio of the sulfonated NASICON-type solid electrolyte, the aminated β-Al2O3, and the aminated porous silica is 1:0.2-0.5:0.1-0.2; coating the functional coating layer slurry on at least one side of the base film to obtain the separator film. The separator film comprises: a base film; and a functional coating layer arranged on at least one side of the base film; wherein the functional coating layer comprises a functional filler and a binder; the functional filler comprises sulfonated NASICON-type solid electrolyte, aminated β-Al2O3, and aminated porous silica; a mass ratio of the sulfonated NASICON-type solid electrolyte, the aminated β-Al2O3, and the aminated porous silica is 1:0.2-0.5:0.1-0.
2. the binder comprises a main binder and a binding aid, the main binder comprises at least one of polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, and polytetrafluoroethylene; the binding aid comprises sulfonated polyether ether ketone, and a sulfonation degree of the sulfonated polyether ether ketone is 40%-60%; a mass ratio of the main binder and the binding aid is 1:0.5-1. the binding aid further comprises polyethylene oxide, and a mass ratio of the sulfonated polyether ether ketone and the polyethylene oxide is 1:0.3-1. the sulfonated NASICON-type solid electrolyte is obtained by treating NASICON-type solid electrolyte with a sulfonation reagent, and a Dv50 of the NASICON-type solid electrolyte is 0.5-3 μm; the aminated β-Al2O3 is obtained by treating β-Al2O3 with an amination reagent, and a Dv50 of the β-Al2O3 is 0.5-3 μm. The separator film satisfies at least one of the following conditions: 1) a mass ratio of the functional filler and the binder is 1:0.1-0.5; 3) the base film is a polyolefin film, a thickness of the base film is 5-20 μm, and an average pore size of the base film is 80-220 nm.
Citation Information
Patent Citations
Inorganic nano particle filler for solid state electrolyte and preparation method of inorganic nano particle filler
CN107134587A
Sodium ion type composite active substance modified diaphragm as well as preparation method and application thereof
CN117996350A